Physiological responses of soybean seeds (Glycine Max L. Merr.) to metal pollutants - Malan, Heather Louise (Department of Biological Sciences, 2023)
Seeds, especially cereals and legumes are a vital component of the human diet and as a result of elevated levels of environmental pollution, seed-bearing crop plants are grown increasingly on contaminated soils. Although several studies have looked at seeds as potential sources of metals that may enter the food chain, very little research has been carried out to examine the effect of such toxicants on the physiology of these plant parts. This study examines the effect of two metal pollutants, namely Cd and Ni, on the development and functioning of soybean seeds. Cadmium was chosen because it is considered to be the most serious of the metal pollutants, is highly toxic to mammals and easily enters the food chain. Nickel, is relatively mobile within plants compared to other metal pollutants and also represents a potential threat to the environment. Soybean plants (cv Crawford) were grown to maturity in a circulating nutrient solution system, which in the case of treatment plants, was amended with either Cd or Ni. From the results of preliminary trials in which the effect of metal pollutant concentration on plant growth and pod production were examined, nutrient solution concentrations of 0.05 mg Cd/litre or 1 mg Ni/litre were used for routine cultivation of the plants (termed metal-treatment plants). Seeds were harvested at four (initially five) different growth stages and the effect of the metal pollutants on size and other developmental parameters investigated. Accumulation and distribution of Cd, Ni and other elements within the seeds was examined. Firstly, by using inductively coupled plasma-atomic emission spectroscopy (ICP-AES) and secondly, at a finer resolution utilising a nuclear rnicroprobe, coupled with proton induced X-ray emission (PIXE). The anatomy and ultra-structure of metal pollutant-treatment seeds was compared with that of control seeds using light as well as transmission electron microscopy (LM and TEM). Possible structural aberrations caused by the presence of Cd or Ni were identified. In another set of experiments, seeds were germinated in solutions of different concentrations of Cd or Ni (termed metal-germinated seeds). The LCso and ECso values for germination and radicle extension respectively, were derived. The effect of metal pollutants on seedling establishment was also examined by cultivating the plants further in nutrient solution containing different concentrations of the metal pollutants. Other seedlings (termed recovery seedlings), subsequent to germination in the metal pollutant, were transferred to the standard control nutrient solution. Uptake of metal pollutant, concentration of photosynthetic pigments and photosynthetic functioning were examined in metal-germinated, recovery and control seedlings. In the final section of the study, chemical speciation in the nutrient solution used for cultivation of metal-treatment plants was modelled using the speciation software MINTEQA2. Percentage bioavailability of the metal pollutants as well as of four nutritionally important metals, Fe, Mn, Mg and Zn was examined. Furthermore, computer simulations were also carried out to model the effect of pH and increasing metal pollutant concentration, on the bioavailability of the abovementioned metals. Addition of even low concentrations of Cd or Ni to the nutrient solution resulted in reduction in root biomass and pod (and hence seed) production. This effect increased with metal pollutant concentration. Cadmium appeared to be more phytotoxic than Ni and lower concentrations of the former were required elicit an equivalent response. Visual toxicity symptoms noted, included red pigmentation in the petioles, chlorosis of the trifoliate leaves followed by the appearance of necrotic areas. In addition, Ni-toxicity symptoms included terminal deformed pods, as well as red spots in the inter-veinal areas of leaves. Both Cd and Ni accelerated plant senescence. Leaf abscission was promoted and in the case of the older growth stages, the rate of pod development was increased relative to that of control pods. Nonetheless, the presence of metal pollutants did not appear to enhance pod abscission during the developmental period examined. In metal-treatment plants, pollutant loads in roots were much higher than in shoots. Cadmium levels in the seeds harvested from these plants were extremely low (approximately 1µg/g.dm) indicating that the metal is excluded from these tissues to a great extent. Nickel was more mobile than Cd, reaching higher levels than the latter in all plant parts and a concentration of approximately 50 µg/g.dm in mature treatment seeds. Pods did not appear to exclude entry of metal pollutants into the seeds and contained similar concentrations as the seeds in the case of Cd and lower concentrations in the case of Ni. Seed concentration of both metal pollutants (when expressed as µg/g.dm) was highest in the youngest growth stages and then decreased with age. Cadmium was found to decrease mean seed size relative to control seeds, but had no effect on the number of seeds per pod. Nickel on the other hand, exerted no effect on size but did reduce the average number of seeds contained in each pod. As a result of reduced mass, the presence of Cd in the nutrient solution reduced the lipid, starch and total N content of seeds harvested from soybean plants grown in such a medium. No significant effect on the quantity of storage reserves could be detected in Ni-treatment seeds. Mature seeds harvested from Cd-treatment plants had lower Fe and Mn, but higher Zn and Mg contents than control seeds. Nickel-treatment seeds also exhibited reduced Fe, Mn and elevated Zn contents, but Mg levels were also reduced. Shifts in seed concentrations of the nutritionally important metals noted above, were also found in pods, most notably a reduction in Fe content. Despite the presence of metal pollutants within the seeds, the extent of germination in metal pollutant-treatment seeds was not impaired compared to control seeds. The rate of germination, however, was depressed slightly in both metal treatments. Examination of metal distribution within seeds using ICP-AES revealed that Cd was localised mainly in the testa and cotyledons, with very little in the axis. Nickel was mainly concentrated in the axis and least in the cotyledons. Cadmium levels in metal-treatment seeds were too low for distribution maps to be made using PIXE and only point analyses were carried out. Overall, these results agreed with those obtained from ICP analysis. Nickel, which accumulated to higher levels within seeds, was mapped successfully using PIXE. The embryo axis appeared to contain the highest concentrations of Ni, particularly in the apical meristem and cortex, but was virtually absent from the root cap area and the central stele. Interesting elemental maps were also obtained for S, Fe and Mn (supplied in the nutrient solution at normal physiological concentrations). Levels of Ni in control seeds were extremely low and could not be mapped. The LC50 and EC50 values for germination and radicle elongation respectively, in the presence of exogenous metal pollutant, were found to be lower for Cd than Ni. This is consistent with the higher phytotoxicity of the former element. Radicle elongation was found to be more sensitive to the presence of exogenous metal pollutants than seed germination. The major effect on seedling establishment was reduction in growth, particularly of the lateral roots. As in the case of mature plants, pollutant loads in the roots of seedlings were higher than in shoots. Recovery seedlings appeared relatively healthy after a period of exposure to metal pollutants, up to a critical concentration of metal pollutant. Nonetheless, although little reduction in the concentration of photosynthetic pigments or the efficiency of photosynthetic functioning was recorded, two weeks after exposure to the metal pollutants, root biomass was still reduced relative to that of control seedlings. The total chlorophyll content of metal pollutant-germinated seedlings decreased at low concentrations of the metal pollutants, but then increased at higher concentrations. It is suggested that this is the result of the combined effects of inhibition of photosynthetic pigment synthesis, coupled to reduced leaf expansion. Metal pollutant-treatment and control seeds did not differ from each other in external appearance nor at the LM level. Slight ultra-structural variations were noted using TEM however, including the presence of vesicles in the nucleoplasm of Cd-treatment cotyledon cells, an increase in the number of crystalloid inclusions in protein bodies (possibly phytate) as well as an increased number of starch grains in the radicle tip cells of Ni-treatment seeds. Further research is needed to confirm these results. Significant ultra-structural changes in metal pollutant-germinated seedlings were noted compared to the controls. From examination of the ultra-structure of such seedlings, both Cd and Ni appeared to affect nuclear functioning, proteolysis, as well as starch grain formation. Cadmium elicited a response at lower concentrations than Ni. It is stressed that these are not necessarily the principal toxic actions of the metals however, as marked structural changes were apparent only at high concentrations. Aberrations to cytoplasm adjacent to the cell wall were also noted in cells from seedlings germinated in the presence of Ni. Computer speciation simulations using MINTEQA2 predicted that in the respective treatment solutions, 87% of Cd, but only 49% of Ni, was in a form suitable for plant uptake. Shifts in seed contents of Mg, Mn and Zn, in response to amendment of the nutrient solution with metal pollutants, could not be explained by changes in chemical speciation in the growth medium. The decrease in Fe content in Ni-treatment seeds on the other hand, may possibly be a consequence of decreased bioavailability of this ion in the nutrient solution. pH was found to exert an effect on the speciation profile of metal pollutants, as well as on that of nutrients. The most marked effect was noted on Nt2. The proportion of metal in this form (the bioavailable form) decreased from 49% to 3% when pH was increased from 6.0 to 7.0. Although plants are able to limit entry of metal pollutants into seeds to some extent, they do still enter these tissues and it is important that the effects on functioning of such plant parts be examined. This study reports preliminary findings on this aspect. Much work remains to be done however particularly with regard to the effect of metal pollutants on the quality of storage reserves, especially proteins. Furthermore, this work should be extended to the seeds of other important crop plants.